Analysing investment product choice in South Africa under the investor lifecycle - Dewald Kellerman; Zandri Dickason Koekemoer; Sune Ferreira (Cogent Economics & Finance, 2020)
Individual investment decision-making theory revolves around the logical choices an investor is expected to make to achieve the maximum return on investments. The investor life cycle theory is often used as a guideline to determine how investors will invest based on their predicted life cycle phase. However, the question remains whether lifecycle investing is still relevant today. The main purpose of the paper is to analyse how demographic factors influence investment product selection for South African banking clients using Big Data. The analysis found that the investment patterns of South African investors strongly contradict the foundational literature of the investor life cycle. South African investors are skewed more towards low-risk investment options like cash, across all age ranges, only investing in higher-risk instruments much later than what the investor life cycle theory suggests. Female investors are especially risk-averse, however, the effect becomes less prominent as income level rises. The risk-averse investment style seen in the findings for all South African investors can be explained by the slow economic growth experienced in South Africa, with investors having less disposable income to invest.
Keywords: D92; G11; J11; 330; banking; demographic factors; investor decision; product choice; South Africa